Unique properties of TCR-activated p38 are necessary for NFAT-dependent T-cell activation - Alam, Muhammad S.; Gaida, Matthias; Debnath, Subrata; Tagad, Harichandra D.; Jenkins, Lisa M. Miller; Appella, Ettore; Rahman, M. Jubayer; Ashwell, Jonathan D. (PLoS biology, 2018)
Nuclear factor of activated T cells (NFAT) transcription factors are required for induction of T-cell cytokine production and effector function. Although it is known that activation via the T-cell antigen receptor (TCR) results in 2 critical steps, calcineurin-mediated NFAT1 dephosphorylation and NFAT2 up-regulation, the molecular mechanisms underlying each are poorly understood. Here we find that T cell p38, which is activated by an alternative pathway independent of the mitogen-activated protein (MAP) kinase cascade and with different substrate specificities, directly controls these events. First, alternatively (but not classically) activated p38 was required to induce the expression of the AP-1 component c-Fos, which was necessary for NFAT2 expression and cytokine production. Second, alternatively (but not classically) activated p38 phosphorylated NFAT1 on a heretofore unidentified site, S79, and in its absence NFAT1 was unable to interact with calcineurin or migrate to the nucleus. These results demonstrate that the acquisition of unique specificities by TCR-activated p38 orchestrates NFAT-dependent T-cell functions.